2019
DOI: 10.1021/acs.jchemed.9b00516
|View full text |Cite
|
Sign up to set email alerts
|

Can We Compare Attitude Scores among Diverse Populations? An Exploration of Measurement Invariance Testing to Support Valid Comparisons between Black Female Students and Their Peers in an Organic Chemistry Course

Abstract: Chemistry education research has sought to understand why students struggle in organic chemistry courses. Beyond the volume and difficulty of the material taught in this course, there are also affective factors, such as attitude toward chemistry, that can influence how students perform. Studies have documented cases in which students of underrepresented minority backgrounds in science fields have less positive attitudes than their majority peers. Thus, in this study, we investigated whether the significant pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 64 publications
1
43
1
Order By: Relevance
“…Few studies, however, have investigated equity in undergraduate chemistry education 1 . In our review of the literature, we found 18 articles that quantitatively measured race order inequities in undergraduate chemistry classrooms [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . Studies that examined race classified students as either majority (White and Asian students) or underrepresented minority students (URM; Black, Hispanic/Latinx, and American Native students).…”
Section: Equity Research In College Chemistry Educationmentioning
confidence: 99%
“…Few studies, however, have investigated equity in undergraduate chemistry education 1 . In our review of the literature, we found 18 articles that quantitatively measured race order inequities in undergraduate chemistry classrooms [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . Studies that examined race classified students as either majority (White and Asian students) or underrepresented minority students (URM; Black, Hispanic/Latinx, and American Native students).…”
Section: Equity Research In College Chemistry Educationmentioning
confidence: 99%
“…Some of them are given below. Rocabado et al (2019) performed measurement invariance testing for the configural, metric, and scalar models comparing black female students and all other students within the traditional and flipped courses for the two-factor model prescribed for the pre and posttests. Their analysis results showed that configural, metric, and scalar invariance was ensured.…”
Section: Discussionmentioning
confidence: 99%
“…Fostering positive student attitudes toward science is an important component to education, and attitude has been shown to correlate strongly with student achievement, persistence, and retention. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] However, while nearly all faculty likely feel competent to assess student skills and knowledge, assessing attitude is often viewed as much more difficult, in part due to their lack of knowledge about attitude. For this reason a few instruments for measuring attitude in science classrooms have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…To address these concerns Xu and Lewis refined the ASCI to make it easier to interpret and to be more valid for a wider range of student populations, as well as a second refinement altering the item order to improve the instrument's factor structure. 1,5 As part of a 5-year goal for the chemistry department to implement and assess pedagogical changes in the lower-division chemistry courses, we were interested in measuring student attitude. However, while we planned on using one of the ASCI variants there were two issues that concerned us.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation